Design and implementation of a test bech system for transfer of pressure sensor data - Fiestas Ugás, Antonio Esteban (Pontificia Universidad Católica del Perú, 2016)
Nowadays, wireless sensor devices have received wide attention across medical application areas; among them, implantable sensing devices are between the most important because of the contribution they make to healthcare and investigations. Nevertheless, the implantable sensing devices must be tested before pre-clinical or in-vivo studies are initiated and test benches are used to perform this previous tests. For this reason, this thesis presents the design and implementation of a test bench to acquire the data from an implantable sensing device that is being developed and will be used to sense the pressure within the thoracic cavity of mammals. The test bench consists on: a sealed container with two connections to increase and sense the internal pressure and is the environment where the sensor will be tested, and a wireless communication system that will acquire and process the sensor’s signal and is consisted of two principal modules that will communicate between them via radio frequency at the biomedical admitted band of 433 MHz using an implemented communication protocol. Finally, the calibration and tests on a pizoresistive pressure sensor have been performed to prove the functionality of the system and the experiments results are presented.
Keywords: Sensores--Implates--Pruebas; Sensores--Radiofrecuencia; https://purl.org/pe-repo/ocde/ford#2.00.00